PERAN SISTEM INFORMASI GEOGRAFI (SIG) SEBAGAI ALAT ANALISIS DALAM ILMU - Imam Arifa'illah Syaiful Huda (Nazharat: Jurnal Kebudayaan, 2019)
Geographic information systems have an important role in the science of history. Geographic information systems are able to integrate various data in the study of history, combine, analyze, and map the results. This journal aims to examine the role of geographic information systems in geography. The method used is descriptive analysis method. The process of searching, collecting, and analyzing data is done by using literature studies from various reliable sources, such as books, journals, scientific articles, and academic archives and taking data on the distribution of cultural heritage in the City of Jambi. The results of the analysis show that the role of geographic information systems in the history of science as a tool to improve spatial or spatial analysis. in detail, the role of geographic information systems in the study of historical science can 1) provide historical data in a spatial form in maps, such as the map of the distribution of cultural heritage in Jambi City, 2) be able to see the comparison of historical facts from several regions, 3) make it easy to associate and correlating with the surrounding environment, 4) regionalization can be made related to the area of ​​power in the past, 5) makes it easy to answer the question "where" and "why there. And understand the relationship between humans and the environment, and how they affect the dynamics of life in the past. Thus, the role of GIS as an analytical tool in history is very important because it is able to provide data spatially and deepen the analysis of historical data.